2016
DOI: 10.1111/codi.13300
|View full text |Cite
|
Sign up to set email alerts
|

Late anastomotic leakage after low anterior resection in rectal cancer patients: clinical characteristics and predisposing factors

Abstract: Late anastomotic leakages that develop after 30 days following low anterior resection are not uncommon and may be associated with the use of radiotherapy. Late leakage should be a different entity from early leakage in terms of the type of leakage, methods of management and subsequent sequelae.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
52
2
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(62 citation statements)
references
References 20 publications
1
52
2
7
Order By: Relevance
“…reported that early symptomatic AL (diagnosed during initial hospital stay, average 8 post-operative days) performed worse than late AL (diagnosed after discharge, average 22 post-operative days) with regard to oral intake, bowel activity and initial hospital stay. Early AL within 30 days after surgery was associated with increased proportions of patients needing relaparatomy (78.8–89% vs 44–55.4%)1213. Several factors may contribute to this discrepancy.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…reported that early symptomatic AL (diagnosed during initial hospital stay, average 8 post-operative days) performed worse than late AL (diagnosed after discharge, average 22 post-operative days) with regard to oral intake, bowel activity and initial hospital stay. Early AL within 30 days after surgery was associated with increased proportions of patients needing relaparatomy (78.8–89% vs 44–55.4%)1213. Several factors may contribute to this discrepancy.…”
Section: Discussionmentioning
confidence: 99%
“…Early anastomotic leakage, defined as AL occurring within 30 post-operative days1216, represents a unique entity requiring more aggressive intervention1213 and causing elevated motality rate compared with late AL. However, since majorities of AL occurred 5–10 days after surgery, cut-point of 30 post-operative days makes late AL rarity17 accounting for less than 4 percent of AL cases as indicated by a Korean team reporting 290 AL from 10477 colorectal carcinomas1.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Characteristics of late leakage (LL) are examined in a few studies without a uniform definition of LL, where the cutoff point is suggested as diagnosis postoperative day (POD) > 21, POD > 30 or after hospital discharge [16][17][18][19][20][21][22][23]. LL incidence varies from 1.3% to 7.7% representing 30-40% of all AL cases [16,19]. The POD to diagnosis of LL ranges from 22 to 99 days, mainly reflecting the discrepancies in LL definition [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%